COST ANALYSIS OF ORAL ANTIHYPERTENSIVE DRUGS: ASSESSING THE EFFECT OF DRUG PRICE CONTROL ORDER IN INDIA - Sharma, Himanshu; Kumar, Amit; Kaur, Samarjeet; Singh, Jayvardhan; Sharma, Garima (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The study focuses on cost analysis of different available brands of oral antihypertensive drugs in India and assesses compliance with their ceiling prices fixed by drug price control order (DPCO). Methods: This is an observational study conducted in the Department of Pharmacology, GSVM Medical College Kanpur, from May to June 2022. The ceiling price of oral antihypertensive drugs was obtained from the DPCO price list 2021 and dosage and prices of the different brands of antihypertensive drugs available in India were obtained from medguideindia.com and Current Index of Medical Specialities-CIMS (Jan–April 2022 edition, India). Thereafter, data analysis of oral antihypertensive drugs was done on Microsoft Excel Office 2019 version. Results: Our study found a total 1575 brands of oral antihypertensive drugs available in market, 34% brands were having prices more than DPCO recommended ceiling price. Maximum price violation was noticed with capsule nifedipine 10 mg (83.33%) and tablet telmisartan 80 mg (60.98%). The maximum cost variation and cost ratio was seen with tablet propranolol 10 mg, that is, 3233.33% and 33.33, respectively, followed by tablet amlodipine 5 mg, that is, 2123.33% and 22.23. Conclusion: Stringent regulation and monitoring of the DPCO price list should be done to ensure that all drugs and especially oral antihypertensive drugs are not sold above the ceiling price set by the order so that the compliance for the drugs is optimized and India could achieve its objective of reducing the prevalence of hypertension to <25% by 2025.